Կրոնաեկեղեցական տերմինների բառակազմական վերլուծություն - Սիլվա Պապիկյան (ՀՀ ԳԱԱ հրատ.)
Словообразовательный анализ армянских религиозно-церковных терминов позволяет выявить наиболее продуктивные модели и закономерности терминообразования. В этой области терминами в основном становятся имена существительные.The word-building analysis of Armenian religious-ecclesiastical terms enables us to identify the patterns of term formation, the most productive models of this subsystem. In this field, terms are mainly coined from nouns.
Keywords: Religion; Language and Literature